The interplay of visual and auditory cues, telepresence, customisation and product information on South African millennials' online sensory experiences and clothing purchase intentions - Erasmus, Alet C. (Aletta Catharina) (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2021.